Teaching presence in telecollaboration. Keeping an open mind. (February 2017) - Turula, Anna
Abstract: This article looks at teaching presence (TP) in online intercultural exchanges (OIE) and its impact on student satisfaction. The question is examined on the basis of a study carried out as action research during two telecollaborative exchanges, both involving EFL teacher trainees from the Department of Modern Languages and Literature of the Pedagogical University of Krakow (PUK), Poland and their foreign partners from: Pädagogische Hochschule, Freiburg (PHF), Germany and University of California, Santa Barbara (UCSB), the United States. The study examines how teaching presence was perceived by the different groups, and how the perceptions influenced the students' evaluation of their telecollaboration. Based on the data gathered by means of (i) an anonymous survey; (ii) two anonymous reflection questionnaires; and (iii) classroom observation it is argued here that in telecollaboration TP is likely to be perceived differently by the individual groups participating in the exchange even if its different aspects had been discussed by the telecollaborating teachers during the set-up phase. This is because online intercultural exchanges are extremely complex and dynamic educational contexts. For the same reason, the relationship between teaching presence and student satisfaction, reported in publications to-date, seems to be less straightforward and more multifaceted in telecollaboration.